Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1186/1471-2199-9-103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Importin 8 (IPO8) as the most accurate reference gene for the clinicopathological analysis of lung specimens

Abstract: Background: The accurate normalization of differentially expressed genes in lung cancer is essential for the identification of novel therapeutic targets and biomarkers by real time RT-PCR and microarrays. Although classical "housekeeping" genes, such as GAPDH, HPRT1, and beta-actin have been widely used in the past, their accuracy as reference genes for lung tissues has not been proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 33 publications
(43 reference statements)
5
42
0
Order By: Relevance
“…Previous studies have shown that GAPDH expression is increased in other human tumors and tumor-derived cell lines from colon, kidney, liver, lung and pancreas (Nguewa et al, 2008;Lau et al, 2000;Gong et al, 1996;Chang et al, 2011;Revillion et al, 2000;Yamagata et al, 1998), which complies with our results. Because of the variability of expression of GAPDH in osteosarcomas, GAPDH expression should not be used as housekeeping genes in analyses on mRNA level and protein level in osteosarcomas studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have shown that GAPDH expression is increased in other human tumors and tumor-derived cell lines from colon, kidney, liver, lung and pancreas (Nguewa et al, 2008;Lau et al, 2000;Gong et al, 1996;Chang et al, 2011;Revillion et al, 2000;Yamagata et al, 1998), which complies with our results. Because of the variability of expression of GAPDH in osteosarcomas, GAPDH expression should not be used as housekeeping genes in analyses on mRNA level and protein level in osteosarcomas studies.…”
Section: Discussionsupporting
confidence: 82%
“…GAPDH might play a role in cancer pathogenesis and translocate to nucleus in response to several anti-cancer agents (Kim et al, 1999). The accumulated results indicated that GAPDH was differentially expressed in prostate, breast, lung, and cervical carcinomas under certain conditions (Nguewa et al, 2008;Lau et al, 2000;Gong et al, 1996;Chang et al, 2011;Revillion et al, 2000;Yamagata et al, 1998;Rienzo et al, 2012). However, the alteration of GAPDH gene expression has little report in osteosarcoma.…”
Section: Introductionmentioning
confidence: 93%
“…Survivin and c-Jun mRNAs were analyzed by semiquantitative PCR, using TaqMan Gene Expression Assays (Applied Biosystems). IPO8 mRNA expression was used as the endogenous control (24).…”
Section: Reverse Transcriptase-pcrmentioning
confidence: 99%
“…A total of 15 commonly used reference genes were evaluated against these criteria, namely: ACTB, beta-2-microglobulin (B2M), GAPDH, betaglucuronidase (GUSB), hydroxymethylbilane synthase (HMBS), hypoxanthine phosphoribosyltransferase 1 (HPRT1), importin 8 (IPO8), phosphoglycerate kinase 1 (PGK1), polymerase RNA II DNA directed polypeptide A 220 kDa (POLR2A), peptidylprolyl isomerase A (PPIA), ribosomal protein large P0 (RPLP0), TATA box binding protein (TBP), transferrin receptor (TFRC), ubiquitin C (UBC), and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta polypeptide (YWHAZ) (Fig. 1 and Table 1) [13][14][15][16][17][18][19][20][21]. The full name, NCBI Gene ID, function, and location of these genes can be found in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%